GE_GERICHTE AC/2435/2010 vom 24. April 2013 - GE Cour de justice (2013)
RÉVOCATION(EN GÉNÉRAL); ÉMOLUMENT DE JUSTICE; MEILLEURE FORTUNE | CPC.404.1; aRAJ.13.B; aRAJ.14.4; aRAJ.22.1; aLPC.181.1; aLPC.181.2.B